The support of the Churches dedicated to the family in its economic crisis - Hanna Tranda (Studia z Teorii Wychowania)
The article shows the ways of helping a family given to it by Churches and Christian organizations in the existing reality. In addition, it shows work with children and young people, which is to prevent their demoralization and to teach them self-reliance and responsibility.